Reasons for large annual yield fluctuations in wild arctic bramble (Rubus arcticus ssp. arcticus) in Finland - Kostamo, Katri; Toljamo, Anna; Kokko, Harri; Kärenlampi, Sirpa; Rita, Hannu (NRC Research Press (a division of Canadian Science Publishing), 2018)
Fluctuations in the yield of wild berries are markedly influenced by weather conditions. However, the cause- effect relationship is often poorly understood. Based on data spanning a 20-year period in Finland, we made an effort to elucidate the influence of different weather conditions on the yield of arctic bramble (Rubus arcticus). We analyzed the regression coefficients of various weather conditions in several regression models using the elaboration approach. Temperature accumulated in July had a positive effect on yield. Yield was negatively influenced by temperature accumulated during the previous summer, rainfall in the October of the previous year, and temperature accumulated in May of the same year. It is notable that the same weather conditions had a positive influence on yield of the same year whereas these conditions had a negative effect on the yield potential of the following year. Compared to traditional analysis methods, the elaboration approach provided a better understanding of the relationship between weather parameters and yield. The rarity of a good yield could be explained by the particular vulnerability of arctic bramble to the negative effects of weather conditions. Some of these factors could be controlled in field conditions when cultivating arctic bramble. The accepted manuscript in pdf format is listed with the files at the bottom of this page. The presentation of the authors' names and (or) special characters in the title of the manuscript may differ slightly between what is listed on this page and what is listed in the pdf file of the accepted manuscript; that in the pdf file of the accepted manuscript is what was submitted by the author.